Radical scavenging activities of the leaf extracts and a flavonoid glycoside isolated from Cineraria abyssinica Sch. Bip. Exa. Rich - Biruk Sintayehu, Kaleab Asres, Y. Raghavendra (Journal of Applied Pharmaceutical Science)
The aqueous decoction of the leaves of Cineraria abyssinica Sch. Bip. exA. Rich (Asteraceae) is used for treatments of myriads of diseases associated with oxidative stress. However, there appear to have been lack reports on its phytochemistry and pharmacological activities. The main purpose of this study was, therefore, to determine the radical scavenging activities of the leaf extracts of C. abyssinica. The aqueous and 80% methanolic crude extracts, chloroform, acetone and methanol fractions of the leaf extracts of C. abyssinica showed potent radical scavenging activities (IC50 = 5.27-12.41 μg/ml). Activity-guided fractionation of the most active, methanol fraction resulted in the isolation of a flavonoidal glycoside, rutin. The structure was assigned on the basis of spectroscopic methods including ultraviolet spectroscopy (UV), infra red (FT-IR), mass spectrometry (MS) and one and two dimensional nuclear magnetic resonance spectrometry (1D- and 2D-NMR). Rutin showed the most potent DPPH scavenging activity (IC50 = 3.53 μg/ml) slightly higher than ascorbic acid (IC50 = 3.57 μg/ml). Acute toxicity studies on the crude extracts showed the nontoxic nature of the plant up to 3 g/kg. Therefore, the present study revealed for the first time the presence of antioxidant phytochemical in the leaves of C. abyssinica that scientifically validated the traditional use and its great potential to be used as a source of antioxidant phytochemicals.
Keywords: free radical scavenging, DPPH, Oxidative stress, C. abyssinica, Asteraceae, Rutin.